Prognostic value of epidermal growth factor-receptor, T138 and T43 expression in bladder cancer. - Ravery, V. (Nature Publishing Group, 1995)
Tumour-associated markers defined by monoclonal antibodies have proven useful to phenotype bladder tumours. In order to evaluate the prognostic value of such markers, we performed an immunohistochemical study on 57 transitional cell carcinomas (23 infiltrative and 34 superficial tumours) and ten healthy bladders using monoclonal antibodies against the external domain of the epidermal growth factor receptor (EGFR) and against the tumour-associated antigens T43, 19A211 and T138. Immunohistochemistry was performed on frozen sections using a two-step alkaline phosphatase method. The staining pattern obtained with each antibody was analysed according to the TNM classification, and results were analysed according to the subsequent clinical course. 19A211 preferentially stained superficial tumours, and T43, T138 and EGFR preferentially stained invasive tumours. Three monoclonal antibodies appeared to have prognostic value, since progression rate survival was significantly (log-rank test) associated with their expression of EGFR (P = 0.017), T138 (P = 0.0009) and T43 (P = 0.031). T138 expression was found to have an independent significant prognostic value using a stepwise logistic regression. T138 antibody may add significant information to classical pathological parameters. IMAGES: